Contrasting historical trends of atmospheric rivers in the Northern Hemisphere - Mengxin Pan; Shineng Hu; Benjamin F. Zaitchik; William K. Pan (npj Climate and Atmospheric Science)
Abstract Previous modeling studies have indicated that Atmospheric rivers (ARs) will become more frequent in the warming climate. However, whether we have experienced more ARs during historical period is less studied. Here, we show that winter AR frequency has significantly increased over the mid-latitude Northern Hemisphere from 1950—2022. Using station-based observations, we confirm that ARs have driven coherent long-term trends in both total and extreme precipitation over land. The warming-induced rise in atmospheric moisture alone accounts for an AR frequency increase of ~0.6–0.8% per decade. AR trends exhibit meridional dipolar patterns over western North America and Europe, governed by positive trends of the Pacific-North America Pattern and North Atlantic Oscillation. The “Pineapple Express” ARs have been suppressed, declining of AR landfalling over the Pacific Northwest. Through atmospheric model analyses, we demonstrate that observed sea surface temperature changes dominate Atlantic AR trends, while exerting minor effects on Pacific AR trends.